Determining the relationship between atherosclerosis and periodontopathogenic microorganisms in chronic periodontitis patients - Bozoglan, Alihan; Ertugrul, Abdullah Seckin; Taspinar, Mehmet; Yuzbasioglu, Betul (Taylor & Francis Ltd, 2017)
Objectives: The aim of this study is to determine the relationship between atherosclerosis and periodontopathogenic microorganisms in chronic periodontitis patients following periodontal treatment. Materials and Methods: A total of 40 patients were included in the study. 20 of these patients diagnosed with atherosclerosis and chronic periodontitis formed the test group. The remaining 20 patients were systemically healthy patients diagnosed with chronic periodontitis and formed the control group. All patients had nonsurgical periodontal treatment. The periodontopathogenic microorganism levels were determined at baseline and at 6 months in microbial dental plaque samples and WBC, LDL, HDL, PLT, fibrinogen, creatinine and hs-CRP levels were determined by blood samples. Results: Statistically significant reduction has been achieved in clinical periodontal parameters following non-surgical periodontal treatment in test and control groups. Following periodontal treatment, WBC, LDL, PLT, fibrinogen, creatinine and hs-CRP levels significantly decreased and HDL levels significantly increased in both test and control groups. Similarly, the periodontopathogenic microorganism levels significantly decreased following periodontal treatment in the test and control groups. A statistically significant positive correlation has been determined between the periodontopathogenic microorganism levels and WBC, LDL, PLT, fibrinogen, creatinine, and hs-CRP levels in the test group. Conclusions: The association between hs-CRP, WBC, LDL, PLT, fibrinogen, creatinine, and the amount of periodontopathogenic microorganisms indicates the possibility that periodontal treatment could decrease the risk atherosclerosis. More studies must be conducted in order for these results to be supported.
Keywords: Atherosclerosis; chronic periodontitis; periodontopathogenic microorganisms; non-surgical periodontal treatment